A Review of Genomic Testing and SDH‐ Deficiency in Gastrointestinal Stromal Tumors: Getting to the GIST - Vaia Florou; Michelle F. Jacobs; Ruth Casey; Denisse Evans; Becky Owens; Margarita Raygada; Sara Rothschild; Samantha E. Greenberg (Cancer Medicine)
ABSTRACT Gastrointestinal Stromal Tumors (GISTs) have seen significant advancements in their diagnosis and management, driven by targeted therapeutic development and molecular testing. The identification of mutations in genes such as KIT and PDGFRA has transformed treatment approaches, particularly through targeted therapies like imatinib, which have improved patient outcomes. This review explores the critical role of genomic testing in GIST, highlighting its importance in accurate diagnosis, treatment planning, and long‐term surveillance for KIT/PDGFRA negative, SDH‐deficient GISTs. SDH‐deficient GISTs arise from mutations or epigenetic changes affecting the succinate dehydrogenase complex. The complexity of SDH‐deficient GISTs, including their association with hereditary syndromes such as Hereditary Paraganglioma‐Pheochromocytoma and/or hypermethylation of the SDHC promoter, underscores the need for comprehensive germline testing. Despite the availability of guidelines, variability exists in genomic testing recommendations across different regions, necessitating a unified approach. This review proposes a simplified algorithm for the genomic workup of GIST, and suggests all individuals with SDH‐deficient GIST, regardless of germline testing result, require monitoring for additional SDHx‐related tumors, given the lack of widely available methylation and full gene SDHA analysis.